2013
DOI: 10.5395/rde.2013.38.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect onStreptococcus mutansand mechanical properties of the chitosan containing composite resin

Abstract: ObjectivesThis study evaluated the antibacterial effect and mechanical properties of composite resins (LCR, MCR, HCR) incorporating chitosan with three different molecular weights (L, Low; M, Medium; H, High).Materials and MethodsStreptococcus (S). mutans 100 mL and each chitosan powder were inoculated in sterilized 10 mL Brain-Heart Infusion (BHI) solution, and was centrifuged for 12 hr. Absorbance of the supernatent was measured at OD660 to estimate the antibacterial activities of chitosan. After S. mutans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 28 publications
(33 reference statements)
1
48
2
4
Order By: Relevance
“…Streptococcus mutans was chosen as the target microorganism because it is a well known major pathogen of caries 20) . These bacteria are small enough to move rapidly and penetrate easily into the dentinal tubules 21) , which may lead to pulp damage.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus mutans was chosen as the target microorganism because it is a well known major pathogen of caries 20) . These bacteria are small enough to move rapidly and penetrate easily into the dentinal tubules 21) , which may lead to pulp damage.…”
Section: Discussionmentioning
confidence: 99%
“…These included: [171] or a broth culture test [144], Methyl thiazolytetrazolium (MTT) assays [11,172], spectrophotometery [38,76,103,104,118], determination of colony forming units [2,16,17,86,96,104,129,160], determination of maximum or minimum inhibitory concentration (MIC) [4,12,13,22,71,169,172], minimum bactericidal concentration [172], direct contact test [39,64,65,77,78,97,109,120,122] and SEM [11,17,103,113,139]. Another method is through viability staining [94], Live/Dead BacLight ® bacterial viability stain has also been was used in some studies to provide data on the amounts of viable bacteria [4,96,104,172].…”
Section: Methods Of Assessing Antimicrobial Properties Of Dental Matementioning
confidence: 99%
“…Other additives to composites and GICs found to be effective against cariogenic bacteria include cetylpyridium chloride, cetrimide [148,150,155,156], benzalkonium chloride [95,146], sodium fusidate [157], 2,2 -bipyridine [158], chitosan [159,160], triclosan [66,149,[161][162][163], propolis [164,165], anthocyanin [166], tetrapod-like zinc oxide whisker (T-ZnOw) [167] and epigallocatechin-2-gallate (EGCG) [11,168,169]. In contrast to most of the other additives, addition of T-ZnOw epigallocatechin-2-gallate resulted in improved mechanical properties [11,167].…”
Section: Other Additivesmentioning
confidence: 99%
“…It has been demonstrated that more microbial plaque is formed on the surface of composite resin restorations compared to amalgam and glass-ionomers 4. As a result of the absence of antibacterial activity in composite resins, attempts have been made to incorporate antibacterial agents such as chlorhexidine, methacryloyloxydodecylpyridinium bromide (MDPB) monomer, ursolic acid and chitosan into composite resins and bonding agents to provide therapeutic effects and antibacterial activity 1,5,6,7. One of the methods suggested is addition of certain antibacterial agents at nano levels to dental composite resins 8,9,10…”
Section: Introductionmentioning
confidence: 99%